Multiobjective autonomous intelligent load control for hybrid single-/three-phase AC/DC smart buildings - Mahdi Ashabani (2020)
Modern distribution grids and smart buildings comprise unbalanced single-phase, three-phase, DC, and constant power loads and battery energy storage systems (BESSs). This paper presents a hybrid single/three-phase multiobjective automated/autonomous intelligent load (MAIL1) control for smart buildings. The main focus is to autonomously and automatically respond to grid disturbances and power imbalances and unbalances by adaptive demand adjustment of various loads. Also, it can realize regulation objectives of a supervisory operator to enable fast building demand control to participate in performance-based frequency regulation markets. Moreover, it is a unified load control strategy for both grid-connected and islanded hybrid single/three-phase AC/DC grids with smooth transition between them without a need for the strategy reconfiguration. The MAIL1 renders an adaptive and continuous demand for single-phase AC and DC loads. The MAIL1 is based on a fundamentally new controller for single-phase voltage source converters (VSCs) by introducing single-phase DC-source synchronous current converter technology, with extra functionalities such as auto-synchronization with single-phase grids and virtual inertia. Extensive real-time hardware-in-loop results are presented to demonstrate the MAIL1 performance.